Sabiedrisko attiecību loma pašvaldību darbā: Latvijas lielo pilsētu analīze - Dzalbe, Krišjānis (Latvijas Universitāte, 2012)
Šajā pētījumā apskatītas attiecības starp valsts pārvaldes organizācijām un ar tām saistīto sabiedrību. Vietējās pašvaldības ir tautai tuvākais valsts pārvaldes līmenis. Lai lēmumu pieņēmēji pēc iespējas labāk varētu noteikt iedzīvotāju patiesās intereses, ir jāzina to viedoklis, ko tie var izteikt iesaistoties pašvaldības procesos. Tomēr, lai iedzīvotāji spētu kvalitatīvi formulēt savu viedokli par procesiem pašvaldībā, tiem ir jābūt informētiem par notiekošo.

For any community to exist its members must communicate. Modern society is characterized by narrower specialization which means that the interaction of people is growing and they are becoming more interdependent. That is why the shaping of these relationships has become a significant area of professional and scholarly activity. State communication or public relations are very important in a democratic state because the foundation of democracy is an informed and involved citizen. The research explains that public relations are necessary for state institutions for two main reasons. Firstly, a government of a democratic state is responsible for its actions to its citizens. Secondly, an effective government administration process requires active participation and support of its citizens.
The Role of Public Relations in Local Government Work: Analysis of Latvian Cities
Keywords: Politikas zinātne (politoloģija)